Living with Chronic Kidney Disease: Illness Perceptions, Symptoms, Coping, and Quality of Life. - Kalfoss, Mary; Schick-Makaroff, Kara; Molzahn, Anita E. (Nephrology Nursing Journal)
The purpose of this study was to explore how illness perceptions, specifically intrusiveness, impact individuals with chronic kidney disease living with dialysis therapy and kidney transplants, and to determine the relationships among illness perceptions, symptoms, coping, and quality of life (QoL). Forty-two individuals on dialysis and with renal transplants completed an online survey. We found strong relationships between illness intrusiveness, symptom scores, and QoL. Illness intrusiveness was highly disruptive to one's financial situation, health, and work. Intrusiveness was also significantly related to individual symptoms, especially tiredness, feelings of well-being, and sleep. Correlations between intrusiveness and QoL were significant. Emotion-focused coping strategies were also significantly associated with intrusiveness. Health professionals can target illness perceptions, symptom burden, and coping strategies to enhance QoL.